Human capital, basic research, and applied research: three dimensions of human knowledge and their differential growth effects - Katharina Werner; Klaus Prettner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We analyze the di fferential growth e ffects of basic research, applied research, and embodied human capital accumulation in an R&D-based growth model with endogenous fertility and endogenous education. In line with the empirical evidence, our model allows for i) a negative association between long-run economic growth and population growth, ii) a positive association between long-run economic growth and education, and iii) a positive association between the level of per capita GDP and expenditures for basic research. Our results also indicate that raising public investments in basic research reduces the growth rate of GDP in the short run because resources have to be drawn away from other productive sectors of the economy. These short-run costs of basic research might be an explanation for the reluctance of governments to increase public R&D expenditures notwithstanding the long-run benefi ts of such a policy.
Keywords: O41; H41; J11; 330